UPAYA SEKOLAH DALAM MENGHADAPI TANTANGAN GLOBALISASI - Atisa As’a; Taufiqurrahman Taufiqurrahman; Abdullah Hamidi (Prima Magistra: Jurnal Ilmiah Kependidikan, 2023)
The purpose of this study is to find out how the efforts of school principals face the challenges of globalization. This research is the result of field research conducted in several sub-districts in Tangerang Regency, this research is descriptive analysis using an empirical approach. Data collection techniques are taken as primary data and secondary data obtained through interviews and observation. With research steps: Data collection, classification and analysis, data processing, conclusions and reports. The informants in this study were 4 people consisting of 3 heads and 1 school supervisor in Tangerang district. The results of the research in the form of descriptive interviews and observations said that: schools must master IT in order to be able to keep up with globalization, school principals are required to have entrepreneurial competence, so that they can give birth to various creativity and innovations from teachers and students in schools, supervision or supervision, and provide training or workshops.